Pengaruh Struktur Kepemilikan, Kebijakan Investasi, Manajemen Laba Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening Pada Sub Sektor Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia - Yunita Budi Alifya Miranti; Mulyanto Nugroho (Penerbit Jurnal Indonesia, 2025)
This study aims to measure the extent to which ownership structure, investment policy, and earnings management influence firm value with financial performance as an intervening variable in the telecommunications sector. The method used is quantitative. The sample used was 19 telecommunications sub-sector companies in 2020-2023. The data used was taken from the company's annual report, then analyzed using SmartPLS software. The results of the study indicate that ownership structure has a negative and insignificant effect on financial performance. Investment policy has a negative and insignificant effect on financial performance. Earnings management has a negative and significant effect on financial performance. Ownership structure has a negative and significant effect on firm value. Investment policy has a positive and significant effect on firm value. Earnings management has a positive and significant effect on firm value. Financial performance has a positive and significant effect on firm value